Design, syntheses, and anti-tuberculosis activities of conjugates of piperazino-1, 3-benzothiazin-4-ones (pBTZs) with 2, 7-dimethylimidazo [1, 2-a]pyridine-3-carboxylic acids and 7-phenylacetyl cephalosporins. Issue 8 (15th April 2016) - Majewski, Mark W.; Tiwari, Rohit; Miller, Patricia A.; Cho, Sanghyun; Franzblau, Scott G.; Miller, Marvin J.
Graphical abstract: Abstract: Tuberculosis (TB) remains one of the most threatening diseases in the world and the need for development of new therapies is dire. Herein we describe the rationale for the design and subsequent syntheses and studies of conjugates between pBTZ and both the imidazopyridine and cephalosporin scaffolds. Overall some compounds exhibited notable anti-TB activity in the range of 2–0.2 μM in the Microplate Alamar Blue (MABA) Assay.